Cultivating Moderate Islam in the Digital Age: Religious Identity Formation at Ma'had Aly Attaqwa, Bekasi - Huda, Ade Naelul; Fitriana, Muhammad Azizan (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to reveal how Ma'had Aly formulated various strategies to strengthen religious moderation among his students. Ma'had Aly is a pesantren higher education that is prepared to produce pesantren cadres. The focus of his education was the study of the yellow book and the texts of classical Islamic scholars. In addition to studying, Ma'had Aly students have the task of helping kyai guide the daily activities of students at Islamic boarding schools. Their high intensity with students can have implications for the religious views of students in Islamic boarding schools so that students are required to have a moderate religious understanding. This research uses qualitative methods in the form of field research by focusing data mining on curriculum, extracurricular and literacy sources of Ma'had Aly. The data was then measured based on four concepts of religious moderation by the Ministry of Religious Affairs of the Republic of Indonesia and analyzed using descriptive analysis. The results showed that Ma'had Aly Attaqwa KH. Noer Alie can be categorized as moderate by making national commitment as the main strategy to strengthen religious moderation. The results also show that the practice of Pancasila, love of the Republic of Indonesia and the practice of patriotic values have been instilled from the beginning by KH. Noer Alie, the founder of Ma'had Aly Attaqwa, was also a freedom fighter and was awarded as a national hero in Indonesia.